Independent and additional value of cardiopulmonary exercise test to the new york heart association classification in heart failure. (11th May 2022) - Moraes Alves De Souza, I; Donelli Da Silveira, A; Stein, R; Santos Pereira Ramos, JV; Sadigursky Ribeiro, R; Meira Pazelli, A; Borges De Oliveira, Q; Sahade Darze, E; Fonteles Ritt, LE
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The Cardiopulmonary Exercise Test (CPET) is the gold standard test for functional assessment in Heart Failure (HF), but it has not been adequately evaluated on top of the New York Heart Association (NYHA) class. Purpose: We aimed to assess the independent and additional value of CPET to NYHA class in patients with HF and ejection fraction (EF) <50%. Our secondary purpose is to assess the performance of CPET variables in patients with better (NYHA I or II) and worse (NYHA III or IV) functional class. Methods: Patients with HF and reduced or mid range ejection fraction (EF) who underwent CPET were followed for the occurrence of the primary end point of death, heart transplantation and left ventricular assist device (LVAD) implant. Cox regression analysis and ROC curve analysis were used to determine independent predictors for the primary outcome and the additional CPET value, respectively. Kaplan–Meier failure curves were created to illustrate time to primary end point. A value of p <0.05 was considered statistically significant. Results: 613 patients were followed for a mean of 30 ± 22 months. Mean age was 56 ± 12 years, 64% were male, mean EF was 30 ± 8%. NYHA as follows: NYHA I 32%, NYHA II 41%, NYHA III 24% and NYHA IV 2.8%. The rate of primary outcomes was 13%. Death occurred in 8.7%, heart transplantation in 4.4% and there were no cases of LVAD´s implantation. Independent predictors of the primary outcome were: EF (HR 0.946; 95% CI 0.918-0.976; p<0.001), NYHA (HR 2.1; 95% CI 1.55-2.73; p<0.001). When peak VO2 was added to the model, it was maintained as an independent predictor (HR 0.90; 95% CI 0.85-0.96; p 0.001), as was the percentage of predicted peak VO2 (HR 0.03; 95% CI 0.007-0.147; p<0.001), VE/VCO2 slope (HR 1.02; 95% CI 1.01-1.04; p 0.011) and CPET score (HR 1.16; 95% CI 1.06-1.27; p<0.001). ROC curve of the predictor model with only NYHA and ROC curves of the models adding the other CPET variables are shown in Figure 1. There was no significant difference between the curves of the model containing only NYHA and the models with the CPET parameters or the CPET score (Table 1). VO2 peak and VE/VCO2 slope were able to discern survival in functional classes I and II (log rank p < 0.001), but were not clearly in classes III and IV (log rank p = 0.113 and p = 0.124 respectively). CPET score was able to discern survival in both groups, in those with the best and worst functional class (log rank p < 0.05). Conclusion: CPET variables were independent predictors of prognosis in HF, even when controlled by NYHA class. Although they have independent value, their additional value was modest and not statistically significant.